3.7k views
4 votes
Help!!!!!!!!!!!!!!!!!!!!!!!!

Help!!!!!!!!!!!!!!!!!!!!!!!!-example-1
User Qasim Khan
by
5.5k points

1 Answer

3 votes

Answer: Choice A) x = -1

=======================================================

Step-by-step explanation:

Look through the table to see when f(x) = g(x)

This happens when both are equal to 1, which is in the fourth row, or when x = -1.

In other words,

  • f(-1) = 1
  • g(-1) = 1

So f(-1) = g(-1)

We can then say the solution to f(x) = g(x) is x = -1.

User ClearCrescendo
by
5.0k points